Studies of the Philopteridae (Mallophaga) from birds of the order Procellariformes: 1: the genus Halipeurus Thompson. - Edwards, Robert L. (1961)
BIB Now: 2630
Inglés
Keywords: Philopteridae; Mallophaga; Procellariformes; Genus Halipeurus